Comparisons Between Infectious and Autoimmune Encephalitis: Clinical Signs, Biochemistry, Blood Counts, and Imaging Findings - Huang CN (Dove Medical Press, 2020)
Chen-Na Huang,* Xiao-Bing Tian,* Shu-Min Jiang, Sheng-Hui Chang, Nan Wang, Ming-Qi Liu, Qiu-Xia Zhang, Ting Li, Lin-Jie Zhang, Li Yang Department of Neurology, Tianjin Neurological Institute, Tianjin Medical University General Hospital, Tianjin 300052, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Yang Tel +86-22-60814536Fax +86-22-60817471Email yangli2001@tmu.edu.cnObjective: Infectious encephalitis (IE) and autoimmune encephalitis (AE) are symptomatically similar in clinic, however essentially different in pathogenesis. Therefore, the objective of this study was to identify specific features to distinguish the two types of encephalitis for early effective diagnosis and treatments through a comparative analysis.Methods: Fifty-nine IE patients and 36 AE patients were enrolled. The patients with IE were divided into viral encephalitis (VE) and bacterial encephalitis (BE) according to the pathogens in cerebrospinal fluid (CSF). Patients with AE were categorized by with or without neural autoantibodies (NAAb). We further divided patients with NAAb into those with neural cell-surface antibodies (NSAbs) or intracellular antibodies (Abs). Clinical features, laboratory data, and imaging findings were compared between AE, IE, and subgroups.Results: Memory deficits, involuntary movement, and seizures were relatively more commonly presenting symptoms in AE patients (p < 0.05). The positive rate of Pandy test was higher in IE patients (p = 0.007). Decreased leukocyte, erythrocyte, and platelet counts in blood were found in IE patients (p < 0.05). Lower serum calcium level was found in VE compared to BE (p = 0.027). Meanwhile, higher serum calcium level was found in patients with NSAbs compared with intracellular Abs (p = 0.034). However, higher levels of LDH in CSF were found in patients with intracellular Abs (p = 0.009). In magnetic resonance imaging, hippocampus lesions were more commonly present in patients with AE (p = 0.042). Compared with AE patients, more IE patients displayed the background electroencephalogram rhythm of slow-frequency delta (p = 0.013).Conclusion: Involuntary movement and memory deficits were more specifically present in AE patients. CSF Pandy, blood routine test and hippocampus lesions detections were potential markers for distinguishing AE and IE. Further, CSF LDH, and serum calcium levels were potentially useful to distinguish subgroups of encephalitis.Keywords: infectious encephalitis, autoimmune encephalitis, cell-surface antibodies, intracellular antibodies, imaging findings